Application Analysis of Zinc Oxide Nanomaterials Based on Quantum Dots in Energy Environment. Issue 5 (January 2021) - Xiao, Yushi
Abstract: Nano-zinc oxide is a new type of multifunctional inorganic material. Nano-ZnO has excellent photocatalytic performance, which can effectively convert harmful pollutants into inorganic substances such as H2 O and CO2, and can effectively remove many refractory substances, thus having great application potential in pollution control. In this paper, ZnO quantum dots are selected as the research object, the nanostructures and various morphologies of ZnO quantum dots are introduced, and various methods for preparing ZnO nanomaterials and their applications in the field of energy and environment are summarized.